Selective synthesis of rebaudioside M2 through structure-guided engineering of glycosyltransferase UGT94D1 - Yang, Lifeng; Yang, Mengliang; Deng, Zhiwei; Hou, Xiaodong; Zheng, Xiangting; Ping, Qian; Rao, Yijian; Shi, Jinsong; Zhang, Yan (Frontiers in Bioengineering and Biotechnology, 2024)
Rebaudioside M2 (Reb M2), a novel steviol glycoside derivative, has limited industrial applications due to its low synthetic yield and selectivity. Herein, we identify UGT94D1 as a selective glycosyltransferase for rebaudioside D (Reb D), leading to the production of a mono β-1,6glycosylated derivative, Reb M2. A variant UGT94D1-F119I/D188P was developed through protein engineering. This mutant exhibited a 6.33-fold improvement in catalytic efficiency, and produced Reb M2 with 92% yield. Moreover, molecular dynamics simulations demonstrated that UGT94D1-F119I/D188P exhibited a shorter distance between the nucleophilic oxygen (OH6) of the substrate Reb D and uridine diphosphate glucose (UDPG), along with an increased O phosphate -C1-O acceptor angle, thus improving the catalytic activity of the enzyme. Therefore, this study provides an efficient method for the selective synthesis of Reb M2 and paves the way for its applications in various fields.